PEMIKIRAN FILOSOFI PENDIDIKAN ISLAM MUHAMMAD IQBAL DAN RELEVANSINYA DENGAN RANAH PSIKOMOTORIK SISWA - Ahmadi, Alfarabi Shidqi (STAI Ma'had Aly Al-Hikam Malang, 2022)
Islamic education for Iqbal must include the totality of human, which in the process must provide the widest possible space for movement and creativity. Muhammad Iqbal, who has a background as a philosopher, often calls of muslims to want to move and not be trapped in boredom. On the other hand, the psychomotor domain is a concept that emphasizes movement intelligence and creativity in skills. This study aims to discover new things of Muhammad Iqbal’s thought and their relevance to the psychomotor domain of students in Islamic education. The research method used is a literature study with a descriptive qualitative approach. The result of this research is that the concept of Islamic education brought by Muhammad Iqbal invites people not only to be satisfied with scientific understanding, but also to take the initiative and move to practice their knowledge. This has relevance to psychomotor which with cognitive understanding capital than follows up with skills or physical movement.